Developing and validating the Caesarean risk assessment nomogram and comparing the effect of cervical ripening balloon, evening primrose oil and misoprostol on childbirth outcomes in term pregnancies: A study protocol - Shahla Hemmatzadeh; Fatemeh Abbasalizadeh; Sakineh Mohammad‐Alizadeh‐Charandabi; Mohammad Asghari Jafarabady; Mojgan Mirghafourvand (Wiley, 2021)
Abstract Aim To develop and validate the nomogram for risk estimation of Caesarean delivery and to compare the effect of cervical ripening balloon, evening primrose oil (EPO) and misoprostol on Bishop Score and duration of the first stage of labour. Design The first phase is a prospective study, and the second phase is a randomized controlled trial. Methods In the first phase, the nomogram will be developed and validated over 300 participants, and in the second phase, the 90 participants will be allocated to three groups: vaginal 25mcg misoprostol, vaginal 4000mg EPO and double‐balloon catheter, through block randomization method. The Bishop score will be evaluated every 4 hr, and if required the same dose will be repeated. Maximum waiting time for balloon is 12 hr if not effective, the catheter will be removed, and other interventions will be done according to guidelines. Discussion The nomogram will help informed decision‐making for women undergoing an induction with an unfavourable cervix and introducing effective low‐complication methods of labour induction can improve the pregnancy outcomes.